Pelatihan Akuntansi, Tingkat Pendidikan, Skala Usaha, Umur Usaha dan Penggunaan Informasi Akuntansi UMKM Kota Surakarta - Nugraheni, Ristia Dian; Rachman , Arif Nugroho (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2024)
The purpose of this study was to determine the effect of accounting training, education level, business scale, and business age on the use of accounting information. This type of research is quantitative research. The population in this study was 11,157 MSMEs in Surakarta City and the sample in this study was 92 samples using purposive sampling. The data used were primary data obtained through questionnaires. The results of this study indicate that accounting training has an effect on the use of accounting information. Education level, business scale and business age do not have an effect on the use of accounting information